EFEKTIVITAS MODEL PEMBELAJARAN JIGSAW BERBANTUAN MEDIA PETA KONSEP UNTUK MENGETAHUI KETERAMPILAN PROSES IPAS SISWA KELAS IV SD MIFTAHUSSA’ADAH - Zulia Prihatiningsih; Siti Masfuah; Rani Setiawaty (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The aim of this research is to determine the science and science process skills after implementing the Jigsaw learning model assisted by concept map media in fourth grade students at Miftahussa'adah Elementary School. One learning model that can be applied to find out science process skills is the Jigsaw model. This research is quantitative research using an experimental method, namely Pre-Experimental in the form of One Group Pretest Posttest Design. The research population was 21 fourth grade students at Miftahussa'adah Elementary School using saturated sampling techniques. Then data collection techniques include observation and documentation. As well as the data analysis used, namely the normality test, paired sample t-test and the N-Gain test with the help of SPSS 25. The results of this research are the N-Gain Score test results for process skills, namely 0.6453 which can be interpreted as quite effective. Based on the research results, it can be concluded that the Jigsaw learning model assisted by concept map media can determine students' science process skills.